Design Of Web-Based Customer Menu Ordering Information System Case Study: Coffee Luck Coffee Shop - Abdurohman, Dudun; Saputra, Eggi Firman; Munahar, Harris (Journal Collabits, 2024)
Technological developments make it easier for users to carry out all tasks such as food and beverage ordering process. One of the technologies used is a computer. Computer is one of the machines in charge to help human work so that the job can be done quickly.  Kedai COFFEE LUCK is one of the places engaged in the culinary that is located in Jl. Ks. Tubun No. 86, RT. 004/RW. 003, Koang Jaya, Pasar Baru, Karawaci, Tangerang City, Banten 15112. Currently the food and beverage ordering process at COFFEE LUCK Store still uses paper for the recording of its order transactions. Conventional system like this is less effective, which raises the problem that the food ordering paper often disappear because the paper ordering only stored in the cashier table, took a long time to build a food ordering report because it must recap the booking paper in one by one, there is still a difference in the amount of payment with the amount of food ordering due to calculation errors. Based on the problems that occur at this time, in need of food and beverage ordering system that can help the cashier in managing the food and beverage order data. This research uses Object Oriented Analysis (OOA) analysis methods and system design using Unified Modelling Language (UML) tools. Collection through observation stages, interviews with stakeholders and library studies. This food and beverage ordering system is made using the PHP programming language and Mysql database. This research resulted in a Web-based customer menu ordering system with the aim to increase time efficiency in managing food and beverage order data and to reduce the difference in payment and booking amounts.